The Development of Primary Effusion Lymphoma-Like Lymphoma in a Patient with Preexisting Essential Thrombocythemia - Yoshiki Uemura; Marina Komoto; Mitsuo Okada (Case Reports in Hematology)
A 71-year-old Japanese male was diagnosed with essential thrombocythemia (ET) with the JAK2 V617F mutation variation, in April 2011. He was mainly treated with hydroxyurea following which the number of platelets was maintained within the normal limit. At age 80, he was hospitalized due to cardiac tamponade. Computed tomography showed no evidence of tumor masses or lymphadenopathy. Pericardial drainage was performed, and cytopathologic examination of the fluid revealed atypical lymphoid cells consistent with an effusion lymphoma of B cell lineage. The pericardial effusion was completely drained, and complete remission was achieved. Ultimately, the patient was diagnosed with primary effusion lymphoma-like lymphoma (PEL-LL). To the best of our knowledge, this is the first report of PEL-LL following ET.